Effect of Cutting parameters, Point angle and reinforcement percentage on surface finish, in drilling of AL6061/Al2O3p MMC - Jadhav, S.S.; Kakde, A.S.; Patil, N.G.; Sankpal, J.B. (Procedia manufacturing, 2018)
The subject of this paper is concerned with the experimental study and the influence of cutting parameters, reinforcement percentage and drill geometry on surface finish, in drilling of Al6061/ Al2O3 Aluminum Metal Matrix Composite. The experimentation is conducted based on Taguchi method, The design have four factors, mixed level design of L-18 array with one column of two level and three columns of three levels had been selected for design. The effects of reinforcement percentage of Al2O3p, point angles of drill bits, Cutting Speed and Feed Rate on Surface Roughness, Mean Force, Torque and Cylindricity had been analyzed here. Moreover the causes of results based on analysis have been discussed. Metal Matrix Composites (MMC) offer numerous thermo-mechanical advantages over standard materials and alloys which make them better candidates in different applications. Their light weight, high stiffness and strength have attracted several industries such as automotive, aerospace, and defense for their wide range of products. However, the wide spread application of Meal Matrix Composites is still a challenge for industry. The hard and abrasive nature of the reinforcement particles is responsible for rapid tool wear and high machining costs. An effort has been made to analyze the machining parameters and surface finish for cost effective solution. The important effects have been discussed and percentage contribution of various process parameters speed, feed, point angle on surface finish, force, torque and Cylindricity have been determined.